Increased proliferative response of lymphocytes from intestinal lymph during long chain fatty acid absorption. - Miura, S (1993)
The effect of long chain and medium chain fatty acid absorption on transport and mitogen-induced blast transformation of lymphocytes in intestinal lymphatics was investigated. Intestinal lymph was collected from mesenteric lymph duct cannulated rats maintained in Bollman's cage. Following the intraduodenal administration of oleic acid (long chain fatty acid) or octanoic acid (medium chain fatty acid), only oleic acid produced a significant increase in lymphocyte flux and enhanced proliferative response of lymphocyte in intestinal lymph, without significant alteration of lymphocyte subsets. These changes appeared to be closely correlated with the appearance of radiolabelled oleic acid. Absorption of a medium chain fatty acid, octanoic acid, most of which appeared to be transported to portal blood, did not produce a significant elevation of lymphocyte flux or increased proliferative response of lymphocyte in intestinal lymph. Pluronic L-81, which is a potent inhibitor of the intracellular formation and secretion of chylomicron, significantly attenuated the increased lymphocyte flux and suppressed the enhancement of lymphocyte responsiveness to PHA in intestinal lymph after stimulation by oleic acid administration. There is a possibility that lymphocyte transport and proliferative response in intestinal lymph during oleic acid absorption are closely related to the process of chylomicron formation and secretion to lymphatics in the intestinal mucosa.